Pengaruh medan elektromagnetik terhadap densitas dan vikositas pada vacuum residue - Akbar Ismi Aziz Pramito; Sri Haryati; Muhammad Djoni Bustan (Jurnal Rekayasa Proses, 2019)
This study tested the effect of electromagnetic field on density and viscosity of vacuum residue from PT. PERTAMINA Refinery Unit III Plaju. The study was conducted using a batch reactor equipped with electromagnetic. The fixed variable in this study is the vacuum residue mass and cracking time, while the variables which are varied are reaction temperature and electromagnetic field. The study was conducted to see the effect of temperatures ranging from 100, 200, 300 and 400oC, and the use of electromagnets with electric currents of 0A, 5A, 10A, 15A and 20A on the density and viscosity of vacuum residue. The experiment compared the effect of the process with electromagnetic field and without electromagnetic field on the density and viscosity of vacuum residue. The results showed that the lowest density (0.874 g/cm3) and viscosity (0.481 cP) were obtained by using 20A electric current electromagnetic field at a temperature of 400oC.